Baited camera survey of deep-sea demersal fishes of the West African oil provinces off Angola: 1200–2500m depth, East Atlantic Ocean. (August 2017) - Jamieson, Alan J.; Linley, Thomas D.; Craig, Jessica
Abstract: Deep-sea demersal fish surveys using baited cameras were undertaken in the West African oil provinces between 1297 m and 2453 m depth in 2002, 2005 and 2008. A total of 29 deployments amounting to 16, 175 images encountered 31 species of bait attending deep-sea fish from 17 families. The extrapolated species richness was 34, indicating that the survey encountered over 90% of bait attending fish species in this area. The dominant species in the area were the morid Antimora rostrata, the synaphobranchids Synaphobranchus cf. kaupii and Simenchelys parasitica, the somniosid Centroscymnus coelolepis and the zoarcid Pachycara crassiceps. An unusually high diversity of bait attending macrourids was observed in addition to patchy aggregations of zoarcids. This study serves as baseline survey data on which to base future long-term environmental monitoring of fish populations in the vicinity of the West African oil provinces. Highlights: Deep-sea demersal fish survey in Licence Block 31 off Angolan Coast. 29 baited camera deployments from 1297 m to 2453 m recorded 31 deep-sea fish species. Dominant families were Synaphobranchidae, Somniosidae, Zoarcidae, Macrouridae, and Moridae. Recommendations for future surveys in the West African oil provinces.